Olympic education in the system of formation of humanistic values of students of the Belarusian State University - Maslovskaya, Yulia I.; Yanovich, Yury A. (University Pedagogical Journal, 2022)
Compliance with modern requirements with important problems of humanisation education plays an important role in the strategic development of higher education. The fate of society in the future depends on the formation of humanistic students. Today the effectiveness of various means of influence of teachers on the socio-psychological qualities of students, moral and value orientations, which are important not only in the sports environment, but also in creative professional activities, helping to easily realise themselves in society, has been revealed. As practice has shown, the participation of student youth in the largest international sports forums and dialogue platforms (within the framework of the Olympic education) was a tangible catalyst that provides noticeable personal growth.
Keywords: humanisation; humanitarisation; Olympic education; students; physical perfection; spiritual values; 2nd European Games